Remote ischemic preconditioning protects against liver ischemia-reperfusion injury via heme oxygenase-1-induced autophagy. - Yun Wang; Jian Shen; Xuanxuan Xiong; Yonghua Xu; Hai Zhang; Changjun Huang; Yuan Tian; Chengyu Jiao; Xuehao Wang; Xiangcheng Li (PLoS ONE, 2014)
Growing evidence has linked autophagy to a protective role of preconditioning in liver ischemia/reperfusion (IR). Heme oxygenase-1 (HO-1) is essential in limiting inflammation and preventing the apoptotic response to IR. We previously demonstrated that HO-1 is up-regulated in liver graft after remote ischemic preconditioning (RIPC). The aim of this study was to confirm that RIPC protects against IR via HO-1-mediated autophagy.RIPC was performed with regional ischemia of limbs before liver ischemia, and HO-1 activity was inhibited pre-operation. Autophagy was assessed by the expression of light chain 3-II (LC3-II). The HO-1/extracellular signal-related kinase (ERK)/p38/mitogen-activated protein kinase (MAPK) pathway was detected in an autophagy model and mineral oil-induced IR in vitro.In liver IR, the expression of LC3-II peaked 12-24 h after IR, and the ultrastructure revealed abundant autophagosomes in hepatocytes after IR. Autophagy was inhibited when HO-1 was inactivated, which we believe resulted in the aggravation of liver IR injury (IRI) in vivo. Hemin-induced autophagy also protected rat hepatocytes from IRI in vitro, which was abrogated by HO-1 siRNA. Phosphorylation of p38-MAPK and ERK1/2 was up-regulated in hemin-pretreated liver cells and down-regulated after treatment with HO-1 siRNA.RIPC may protect the liver from IRI by induction of HO-1/p38-MAPK-dependent autophagy.